The Relationship between ESG Scores and Corporate Governance Practices on Corporate Financial Stability in the Infrastructure Sector in Indonesia - Judijanto, Loso; Destiana, Rina (Westscience Press, 2024)
This study examines the relationship between Environmental, Social, and Governance (ESG) scores and corporate governance practices on corporate financial stability in Indonesia's infrastructure sector. Using a quantitative approach, data were collected from 60 infrastructure companies through a Likert-scale questionnaire (1-5) and analyzed using SPSS version 25. The findings reveal that both ESG scores and corporate governance practices significantly and positively influence corporate financial stability, with governance practices showing a stronger impact. The results underscore the synergistic relationship between ESG and governance, highlighting their importance in mitigating risks and enhancing resilience in high-capital industries like infrastructure. These insights provide actionable recommendations for corporate leaders and policymakers to strengthen governance and sustainability practices, fostering long-term financial stability and competitiveness.